Internal artificial vagina (IAV) to assess breeding behavior of young Bos taurus and Bos indicus bulls - Cruz F.B.* (2011)
Bull breeding soundness evaluation (BBSE) usually neglects the libido and mating ability evaluation. The internal artificial vagina (IAV) permits semen sampling, as well as mating ability evaluation. Few studies have been performed using IAV with young bulls and there are none with Bos indicus bulls. The present study evaluated sexual behavior, mating ability and semen quality in young Bos taurus (Devon) and B. indicus (Nellore) bulls using the IAV device. In the first experiment, 52 Devon bulls, 18-25 months old were observed, and the behavior and mating ability recorded over a 10-min period within a restrained mount-cow with an IAV inserted. In the second experiment, 20 Nellore bulls, 20-30 months old were evaluated over a 20. min period. Of the 52 Devon bulls, 45 (86.5%) had semen recovered with the IAV, 31 (69.0%) were considered satisfactory. Nellore bulls exhibited a different sexual behavior, with 10 bulls not showing any interest in the females. Four bulls demonstrated sexual interest only once, e.g., sniffing, two showed interest on more than one occasion, and four had more than two mounts or mounting attempts. None out of the Nellore bulls was collected with IAV. The IAV was an effective and welfare-promoting animal technology for the evaluation of semen quality and mating ability of B. taurus bulls. However, the IAV was not adequate for young Nellore bulls, probably due to their quiescent sexual behavior and delayed sexual maturity. Further studies are needed to evaluate the performance of the IAV for older Nellore bulls. © 2011 Elsevier B.V.